2018
DOI: 10.1186/s13567-018-0577-z
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle disease virus-attenuated vaccine LaSota played a key role in the pathogenicity of contaminated exogenous virus

Abstract: Newcastle disease virus (NDV)-attenuated vaccine has been widely used since the 1950s and made great progress in preventing and controlling Newcastle disease. However, many reports mention exogenous virus contamination in attenuated vaccines, while co-contamination with fowl adenovirus (FAdV) and chicken infectious anaemia virus (CIAV) in the NDV-attenuated vaccine also emerged in China recently, which proved to be an important reason for the outbreaks of inclusion body hepatitis–hydropericardium syndrome in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Incomplete inactivation of killed NDV vaccine may lead to infections in animals. Studies have found some attenuated vaccines to be contaminated with exogenous viruses, including fowl adenovirus and chicken infectious anemia virus, [19,31]. In addition, traditional vaccines have the disadvantage of needing to be kept cold during shipping, which is difficult in some developing countries and remote rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete inactivation of killed NDV vaccine may lead to infections in animals. Studies have found some attenuated vaccines to be contaminated with exogenous viruses, including fowl adenovirus and chicken infectious anemia virus, [19,31]. In addition, traditional vaccines have the disadvantage of needing to be kept cold during shipping, which is difficult in some developing countries and remote rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…The FAdV-4 strain ( F-Vac ) used in this study was isolated from a Newcastle disease virus attenuated vaccine and stored in our laboratory at −80°C, and it can induce obvious HHS in specific-pathogen-free chicken ( Su et al., 2018a , b ). Detailed isolation and identification procedures can be found in the previous report ( Su et al., 2018a ).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is still not clear how the strain spread in China at an incredible fast speed. Previous studies have shown that the use of attenuated vaccines contaminated with FAdV-4 may be an important reason for the outbreak of HHS in some flocks ( Su et al., 2018a , b ). However, the complete genome of the vaccine-contaminated strain is not provided, which hinders the further determination of its relationship with other identified strains.…”
Section: Introductionmentioning
confidence: 99%
“…15 The spread of the outbreaks was exacerbated mostly by contamination by both FAdV and CAV. 16 The suggested vaccine associated with these outbreaks is in use in the United States, although we are not aware of any contamination issues. The spread of FAdV through contaminated vaccines does not seem likely to be a primary route of exposure for backyard chickens, given that small hobby flocks tend to have minimal vaccination strategies.…”
Section: Brief Reportmentioning
confidence: 99%